(3HZjI GdeSJajO aj CNHGQ eOjfI RHjOs - (3YHO GdQMef Hf Ydj Hf eMeO GdTjHGfqj GdRHjOj GdTGaYqj, hLjg GdOjf, GdeYQha H` GHf GdnqOrjnHY,J (B944 (3g` s
(3ChdgG (B:s
(3GdMeO ddg Gdedc hGdedchf agRe GdLdhOi YHO Gddg GdePchQ hef eYg hONd s
(3BNQgG (B:s
(3hjLeY dg Hjf fUQg GdYRjR haJMg GdeHjf hjLYd cdeI Gdedc HGbjg Je GdcJGH hGdMeO ddg s
(3GfXQ GdbSe GdKGfi ef GdJGQjN Qbe (B593s
(3QJHg Ydi ebOeI hYTQ GHhGHs
(3fSNI KGfjIs
(3bQf GdfSN (B:s
(3GdbQf GdMGOj YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GdJGQjNs